Precision Lactobacillus reuteri therapy attenuates luminal distension-associated visceral hypersensitivity by inducing peripheral opioid receptors in the colon. Issue 12 (December 2020) - Hegde, Shrilakshmi; Lin, You-Min; Fu, Yu; Savidge, Tor; Shi, Xuan-Zheng
Abstract : Abstract: Luminal distension and abdominal pain are major clinical hallmarks of obstructive bowel disorders and functional bowel disorders linked to gut dysbiosis. Our recent studies found that chronic lumen distension increased visceral sensitivity and decreased abundance of gut commensal Lactobacillus reuteri in a rodent model of partial colon obstruction (OB). To establish causation, we performed precision microbial therapy to assess whether recolonization of L. reuteri prevents visceral hypersensitivity in lumen distension, and if so, to identify the gut-microbiota mechanism. Lumen distension was induced in Sprague-Dawley rats by implanting an OB band in the distal colon for up to 7 days. L. reuteri strains or vehicle were gavage ingested 1 × 10 7 colony-forming units/g daily starting 2 days before OB. L. reuteri rat strains that were able to recolonize obstructed colon significantly improved food intake and body weight in OB rats, and attenuated referred visceral hyperalgesia measured by the withdrawal response to von Frey filament applications to the abdomen. Mechanistically, L. reuteri treatment attenuated hyperexcitability of the dorsal root ganglia neurons projecting to the distended colon by promoting opioid receptor function in affected tissues. The expression of µ, δ, and κ opioid receptors was significantly downregulated in colonic muscularis externae and sensory neurons in OB rats. However, L. reuteri treatment prevented the loss of opioid receptors. Furthermore, administration of peripheral opioid receptor antagonist naloxone methiodide abolished the analgesic effect of L. reuteri in OB. In conclusion, precision L. reuteri therapy prevents lumen distension-associated visceral hypersensitivity by local bacterial induction of opioid receptors.